Gender Construction in Pesantren in Johor (Malaysia) and Central Java (Indonesia) - Tri Marhaeni P. Astuti (Humaniora, 2010)
This article investigates gender construction in Islamic boarding schools or 'pesantren' Semarang, Indonesia (Al-Islah and Al-Anshor) and Johor, Malaysia (Mahad and Marsah). It was found that despite their different countries and customs, the schools in Indonesia and Malaysia show some similarities, especially in terms of the teaching of Islamic jurisprudence and thei perceptions of the rights of men and women as explained in the Qur'an. HOwever, they differ, especially in terms of the implementation of these in their daily lives. In Johor, Malaysia, men are responsible for activities outside of the households whereas women are in charge of the domestic chores. In Semarang, Indonesia, however, women, despite their household responsibilities, can also work outside. In addition, in terms of polygamy, most people in Johor support it as long as it does not break any religious laws.